Dilema Etik di Rumah Sakit saat Keterbatasan Sumber Daya dalam Pandemi COVID-19 - Susilo, Astrid Pratidina; Ervin Dyah Ayu Masita Dewi (Keluwih: Jurnal Sosial dan Humaniora, 2021)
Abstract—COVID-19 has induced a global health problem with the impact to different aspects of human life. If numbers of patients are increasing beyond the healthcare capacity, the constraint of resources will stimulate ethical dilemma. In hospitals, the availability of drug, hospital beds, trained health professionals, and personal protective equipment are not enough to response patients’ needs. To face this condition, health professionals and hospitals need ethical guidance to allocate resources. This article aims to discuss the guides that are available in the international literature and to recommend Advanced Care Planning as an additional measure to manage the scarcity or resources. The communal culture or Indonesia may contribute to the ethical challenges through the ‘in-group’ and ‘out-group’ phenomenon. Keywords: COVID-19, resource allocation, ethical dilemma Abstrak—Pandemi COVID-19 telah menyebabkan masalah kesehatan global yang berdampak ke berbagai aspek kehidupan manusia. Jika angka penderita melebihi kapasitas sistem layanan kesehatan, terjadi keterbatasan sumber daya yang akan menimbulkan dilema etik. Di rumah sakit, ketersediaan obat, tempat tidur, tenaga kesehatan terlatih, alat pelindung diri tidak cukup untuk merespons kebutuhan pasien. Untuk menghadapi kondisi ini, tenaga kesehatan dan rumah sakit membutuhkan panduan etika untuk mengalokasikan sumber daya. Artikel ini bertujuan untuk mendiskusikan panduan-panduan yang ada di internasional serta mengusulkan Advanced Care Planning sebagai pendekatan tambahan dalam mengelola keterbatasan sumber daya. Budaya komunal di Indonesia dapat menambah tantangan etika di Indonesia melalui fenomena ‘dalam’ dan ‘luar’ kelompok. Kata kunci: COVID-19, alokasi sumber daya, dilema etik